An investigation of personal mobility device (PMD) accidents - Ng, Lionel Rong Quan (Nanyang Technological University, 2022)
It is commonplace for Personal Mobility Devices (PMDs), which in this study refers to Electric Bicycles (E-Bikes) or Electric Scooters (E-scooters), to be able to accommodate a pillion rider, a person that travels in a seat, often, behind the main rider. PMD accidents which may involve pillion riders and pedestrians have reportedly, often lead to severe injuries or death in certain cases. However, there has been insufficient scientific studies of PMD-pedestrian collisions, especially when pillion riders are involved, to greater understand the effects of pillion riders on pedestrian injuries and injuries to pillion riders. The objective of this project is to study the severity of the injury and its mechanism, inflicted on the pedestrian and the pillion riders in collisions between (i) E-Bikes and pedestrians, when a pillion rider is involved. The study will be conducted with the use of an accident reconstruction software, Virtual CRASH (vCRASH). Multiple accident scenarios were generated based on different variables, impact angles, impact offset distance, impact velocity, pedestrian size. The head impact velocity and throw distance of the subjects would then be used to evaluate the head impact velocity and simulation footage would be used to determine the fall mechanics of the subjects. Results have shown the correlation between the vehicle impact velocity and the head impact velocity of the pedestrian, rider and pillion. Simulations have also revealed the difference in fall mechanics between variables. To conclude, the objectives of this study was achieved, and results obtained will be useful to authorities governing the use of PMDs. Recommendations for future studies of this project was also provided.